Coated Cutting Tools
Patent Information
- Application Number
- JP2023175169
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-21
- Filing Date
- 2023-10-10
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-02-19
AI Technical Summary
【0011】 本発明によれば、耐久性に優れる被覆工具を得ることができる。
Smart Images

Figure 0007636492000006 
Figure 0007636492000007 
Figure 0007636492000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a coated tool applied to tools such as dies and cutting tools. This application claims priority based on Japanese Patent Application No. 2020-028679, filed on February 21, 2020, the contents of which are incorporated herein by reference. [Background technology]
[0002] Nitrides or carbonitrides of Al and Ti (hereinafter sometimes referred to as AlTiN or AlTiCN) are films with excellent wear resistance and heat resistance, and are widely used as coated dies and coated cutting tools. In general, in AlTiN and AlTiCN, as the Al content increases, the amount of AlN with a brittle hexagonal close-packed structure (hereinafter sometimes referred to as hcp structure) increases. As the amount of AlN with the hcp structure increases, the hardness of the hard coating decreases, and the tool performance decreases (Patent Document 1).
[0003] In AlTiN or AlTiCN, even if only the peak intensity of the face-centered cubic lattice structure (hereinafter sometimes referred to as fcc structure) is measured by X-ray diffraction, the microstructure may contain hcp AlN. In addition, in harsh environments such as high hardness of the workpiece or high-speed cutting, the tool performance tends to decrease due to an increase in hcp AlN contained in the microstructure of the hard coating. In response to this problem, the applicant of the present application has proposed a coated cutting tool suitable for cutting high-hardness steel, in which Al-rich AlTiN or AlTiCN with reduced hcp AlN contained in the microstructure is provided on an intermediate coating formed by titanium bombardment (Patent Document 2).
[0004] In the specific examples of Patent Documents 1 and 2, the arc ion plating method is used among the physical vapor deposition methods. The physical vapor deposition method is applied to coated cutting tools that perform milling, in order to impart residual compressive stress to the hard coating to enhance chipping resistance. Among the physical vapor deposition methods, the arc ion plating method is widely used because it has a high ionization rate of the target and can obtain a hard coating that has excellent adhesion to the substrate. In the arc ion plating method, the target components are evaporated by arc discharge to form the coating, so the hard coating inevitably contains many droplets of several micrometers.
[0005] On the other hand, among physical vapor deposition methods, the sputtering method, in which a target component is sputtered with argon gas to coat the surface, is less likely to generate droplets, and therefore a smooth hard coating can be obtained. However, the sputtering method has a lower ionization rate of the target than the arc ion plating method, so voids are easily formed inside the hard coating, and the adhesion between the hard coating and the substrate is poor. Therefore, hard coatings coated by the sputtering method generally tend to be less durable than hard coatings coated by the arc ion plating method. For small diameter tools, the effect of droplets on the surface of the hard coating becomes greater relative to the tool diameter. Therefore, if a hard coating with excellent durability can be applied by the sputtering method, further improvements in tool performance can be expected for small diameter tools such as small diameter end mills with tool diameters of 3 mm or less, and even 2 mm or less.
[0006] In recent years, in order to increase the ionization rate of the target, coated cutting tools coated with AlTiN by a high-power sputtering method in which the power applied to the target is momentarily increased have begun to be proposed (Patent Documents 3 to 5). In Reference 6, it is shown by X-ray diffraction that Al-rich AlTiN coated by the high-power sputtering method has an fcc structure. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 8-209333 [Patent Document 2] International Publication No. 2014 / 157688 [Patent Document 3] JP 2011-189419 A [Patent Document 4] JP 2013-202700 A [Patent Document 5] International Publication No. 2017 / 170536 [Patent Document 6] WO 2019 / 48507 Summary of the Invention [Problem to be solved by the invention]
[0008] Regarding Al-rich AlTiN coated by the sputtering method, there has been no sufficient study on reducing the unavoidable argon contained therein and the hcp AlN contained in the microstructure, and there was room for improvement in the durability of the coated tool. In view of the above circumstances, an object of the present invention is to reduce defects contained within a hard coating mainly composed of Al-rich AlTiN or AlTiCN coated by a sputtering method, thereby improving the durability of the coated tool. [Means for solving the problem]
[0009] The present invention relates to a substrate and a coating having a hard coating on the substrate. cutting A tool, The hard coating is a sputtering coating, The hard coating contains aluminum (Al) at 65 atomic % or more and 90 atomic % or less, titanium (Ti) at 10 atomic % or more and 35 atomic % or less, and the total of aluminum (Al) and titanium (Ti) at 85 atomic % or more, based on the total amount of metal (including metalloid) elements; It is a nitride or carbonitride containing argon (Ar) at 0.20 atomic percent or less based on the total amount of metallic elements (including metalloids) and nonmetallic elements, In an intensity profile obtained from a selected area diffraction pattern under a transmission electron microscope, the hard coating satisfies the relationship Ih×100 / Is≦12, where Ih is the peak intensity due to the AlN (010) plane of the hexagonal close-packed structure, and Is is the sum of the peak intensities due to the AlN (111) plane, TiN (111) plane, AlN (200) plane, TiN (200) plane, AlN (220) plane, and TiN (220) plane of the face-centered cubic lattice structure, and the peak intensities due to the AlN (010) plane, AlN (011) plane, and AlN (110) plane of the hexagonal close-packed structure.
[0010] The hard coating preferably has a structure having a region mainly made up of relatively coarse particles and a region mainly made up of relatively fine particles. The average crystal grain size in the region mainly composed of relatively coarse grains is preferably 1.2 to 4.0 times the average crystal grain size in the region mainly composed of relatively fine grains. In the region mainly made up of relatively coarse particles, the value of Ih×100 / Is is preferably 0 to 8, and in the region mainly made up of relatively fine particles, the value of Ih×100 / Is is preferably 4 to 12. The hard coating is preferably provided directly on the substrate. The hard coating preferably has a nanoindentation hardness of 30 GPa or more and an elastic modulus of 500 GPa or more. Effect of the Invention
[0011] According to the present invention, a coated tool having excellent durability can be obtained. [Brief description of the drawings]
[0012] [Figure 1] 1 is an example of a cross-sectional photograph taken by a transmission electron microscope of a hard coating having a region mainly made up of relatively coarse particles and a region mainly made up of relatively fine particles. [Diagram 2] FIG. 2 is an enlarged photograph of a region in FIG. 1 that is dominated by relatively coarse particles. [Diagram 3] FIG. 3 is a diagram showing the selected area diffraction pattern in FIG. 2. [Figure 4] FIG. 4 is a diagram showing the intensity profile of the selected area diffraction pattern shown in FIG. [Diagram 5] 2 is an enlarged photograph of a region in FIG. 1 that is dominated by relatively fine particles. [Figure 6] FIG. 6 is a diagram showing the selected area diffraction pattern in FIG. 5. [Figure 7] FIG. 7 is a diagram showing the intensity profile of the selected area diffraction pattern shown in FIG. 6. [Figure 8] 1 is an example of a cross-sectional observation photograph taken by a transmission electron microscope in a comparative example. [Figure 9] FIG. 9 is a diagram showing the selected area diffraction pattern in FIG. [Figure 10] FIG. 10 is a diagram showing the intensity profile of the selected area diffraction pattern shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present inventors have found that the durability of a coated tool coated with an Al-rich nitride or carbonitride of Al and Ti by a sputtering method can be improved by controlling the content ratio of argon (Ar) relative to the total amount of metal elements and nonmetal elements and reducing the amount of hcp AlN at a micro level. Hereinafter, the details of the embodiment of the present invention will be described. The coated tool of this embodiment is a coated tool having nitrides or carbonitrides of Al and Ti on the surface of a substrate. The coated tool of this embodiment can be applied to dies and cutting tools. In particular, it is preferable to apply the coated tool to small-diameter end mills having a tool diameter of 3 mm or less, and more preferably 2 mm or less.
[0014] <Base material> In this embodiment, the substrate is not particularly limited. Cold work tool steel, hot work tool steel, high speed steel, cemented carbide, etc. may be appropriately applied depending on the application. The substrate may be previously subjected to nitriding treatment, metal bombardment treatment, etc. Also, mirror finishing may be performed by lapping, etc.
[0015] <Aluminum (Al), Titanium (Ti)> The hard coating according to the present embodiment is a nitride or carbonitride, and contains aluminum (Al) at 65 atomic % or more and 90 atomic % or less, titanium (Ti) at 10 atomic % or more and 35 atomic % or less, and the total of aluminum (Al) and titanium (Ti) at 85 atomic % or more, based on the total amount of metal (including metalloid) elements. Nitrides or carbonitrides mainly composed of Al and Ti are a type of film that is excellent in balance between wear resistance and heat resistance, and also have excellent adhesion to the substrate, and the heat resistance of the hard coating is further improved by increasing the content ratio of Al in particular. In addition, by increasing the content ratio of Al, an oxidation protective coating is easily formed on the tool surface, and the coating structure becomes fine, so that the wear of the hard coating due to welding is easily suppressed.
[0016] In order to fully exert the effect of adding Al, the hard coating according to this embodiment has an Al content of 65 atomic % or more when the total metal elements (including metalloids; the same applies below) are taken as 100 atomic %. More preferably, the Al content is 70 atomic % or more. More preferably, the Al content is 75 atomic % or more. On the other hand, if the Al content is too high, the hcp structure AlN increases, reducing the toughness of the hard coating. Therefore, in the hard coating according to this embodiment, when the total metal elements are taken as 100 atomic %, the Al content is 90 atomic % or less. More preferably, the Al content is 85 atomic % or less.
[0017] In the hard coating according to this embodiment, when the total metal elements are taken as 100 atomic %, the Ti content is 10 atomic % or more. More preferably, the Ti content is 15 atomic % or more. This allows the hard coating to have excellent wear resistance. On the other hand, if the Ti content in the hard coating is too high, it is difficult to obtain the above-mentioned effect of increasing the Al content. Therefore, in the hard coating according to this embodiment, when the total metal elements are taken as 100 atomic %, the Ti content is 35 atomic % or less. More preferably, the Ti content is 30 atomic % or less. More preferably, the Ti content is 25 atomic % or less.
[0018] In order to impart excellent durability to the coated tool, the hard coating according to this embodiment contains Al and Ti in total at 85 atomic % or more, when the total metal elements are taken as 100 atomic %, and more preferably, the total of Al and Ti is 90 atomic % or more. The hard coating according to this embodiment may be a nitride or carbonitride of Al and Ti. Nitride is preferable, as it is a film type with better heat resistance. The content ratio of the metal element in the hard coating according to the present embodiment can be measured by using an electron probe microanalyzer (EPMA) for the mirror-finished hard coating. In this case, for example, after mirror-finishing the hard coating surface, the content ratio can be determined from the average of five analysis points with a diameter of about 1 μm.
[0019] <Metal elements other than aluminum (Al) and titanium (Ti)> The hard coating according to the present embodiment may contain metal elements other than Al and Ti. For example, the hard coating according to the present embodiment may contain one or more elements selected from elements of Groups 4a, 5a, and 6a of the periodic table, and Si, B, and Y, for the purpose of improving wear resistance and heat resistance. These elements are generally contained in order to improve the coating properties of the coated tool. Metal elements other than Al and Ti can be added to the extent that the durability of the coated tool is not significantly reduced. However, if the content ratio of metal elements other than aluminum (Al) and titanium (Ti) is too high, the durability of the coated tool may be reduced. Therefore, when the hard coating according to the present embodiment contains metal elements other than aluminum (Al) and titanium (Ti), the total content ratio is preferably 12 atomic % or less.
[0020] <Argon (Ar)> The hard coating according to this embodiment contains argon (Ar) in an amount of 0.20 atomic % or less relative to the total amount of metallic elements and non-metallic elements. The occurrence frequency of droplets, which are defects in the hard coating, can be reduced by applying a sputtering method. On the other hand, in the sputtering method, the target components are sputtered using argon ions, so the hard coating coated by the sputtering method contains a fair amount of argon. In particular, argon tends to concentrate at the grain boundaries, and the argon content tends to increase when the grain size becomes fine. As in the hard coating according to this embodiment, when the Al content is increased, the structure of the hard coating tends to become finer, and the grain boundaries increase, making it easier to contain a large amount of argon. When the argon content increases, the bonding force between particles at the grain boundaries decreases, so in order to impart excellent durability to the coated tool, it is effective to increase the Al content of the hard coating while keeping the argon content at a certain level or less. Specifically, the hard coating according to this embodiment contains argon at 0.20 atomic % or less with respect to the total amount of metal elements and nonmetal elements. More preferably, the hard coating of this embodiment contains argon at 0.10 atomic % or less. The hard coating according to this embodiment may contain a rare gas other than argon if sputtering is performed using a mixed gas containing a rare gas other than argon.
[0021] In the sputtering method, if the content ratio of argon in the hard coating is made as close as possible to 0 atomic %, the flow rate of argon becomes too small, making sputtering unstable. Even if the content ratio of argon approaches 0 atomic %, basic properties of a hard coating applied to a tool, such as toughness, heat resistance, and wear resistance, may be impaired. Although the lower limit of the content ratio of argon in the hard coating according to this embodiment is not particularly limited, it is preferable to contain 0.02 atomic % or more of argon in order to stabilize the sputtering method and ensure basic coating properties of a hard coating applied to a coated tool.
[0022] <Nitrogen (N)> In the hard coating according to this embodiment, when the content ratio of metal (including metalloid) elements to nitrogen, oxygen, carbon, and argon is taken as 100 atomic %, the ratio N / Me of the content ratio N of nitrogen element to the content ratio Me of metal (including metalloid) elements is preferably 1.0 or more. This tends to result in sufficient formation of nitrides in the hard coating, leading to excellent durability. However, if the content ratio of nitrogen becomes too high, the hard coating becomes susceptible to self-destruction, so the ratio N / Me is preferably 1.1 or less.
[0023] The nitrogen and argon content ratios of the hard coating according to this embodiment can be measured by using an electron probe microanalyzer (EPMA) for the mirror-finished hard coating in the same manner as in the measurement of the content ratios of the metal elements described above. As in the measurement of the content ratios of the metal elements described above, the nitrogen and argon content ratios can be determined by averaging five analysis points in an analysis range of about 1 μm in diameter after mirror finishing. The hard coating according to this embodiment may contain trace amounts of argon, oxygen, and carbon as non-metallic elements in addition to nitrogen.
[0024] <Oxygen (O), Carbon (C)> The hard coating according to the present embodiment is a nitride or carbonitride, but may contain a small amount of oxygen. Oxygen forms a small amount of oxide in the hard coating, which may reduce the toughness. If the oxygen inevitably contained in the hard coating can be reduced, the toughness of the hard coating can be increased. In addition, even in the case of a nitride, a small amount of carbon may be contained.
[0025] In the hard coating according to this embodiment, in order to minimize the trace amount of oxides contained in the hard coating, the oxygen content is preferably 5.0 atomic % or less. More preferably, the oxygen content is 4.0 atomic % or less. Furthermore, since the durability of the coated tool tends to decrease if the hard coating contains too much carbide, the carbon content is preferably 5.0 atomic % or less. More preferably, the carbon content is 3.0 atomic % or less.
[0026] <Crystal structure> The hard coating according to this embodiment has a microstructure containing a small amount of hcp AlN, which improves the durability of a coated tool having a high Al content. To quantitatively determine the hcp structure AlN present in the microstructure of the hard coating, a selected area diffraction pattern is obtained using a transmission electron microscope for the processed cross section of the hard coating, and the intensity profile obtained from the selected area diffraction pattern is used. Specifically, the brightness of the selected area diffraction pattern is converted, and an intensity profile is obtained from the selected area diffraction pattern with the horizontal axis representing the distance (radius r) from the center of the (000) surface spot and the vertical axis representing the integrated intensity (arbitrary unit) for one revolution around a circle at each radius r. Then, the relationship Ih×100 / Is is evaluated in the intensity profile of the selected area diffraction pattern obtained by the transmission electron microscope. In this evaluation, the background value of the intensity profile is removed. The measurement location is a cross section in the film thickness direction. Ih and Is are defined as follows:
[0027] Ih: Peak intensity due to the (010) plane of hcp AlN. Is: The sum of the peak intensities due to the (111) plane of AlN, the (111) plane of TiN, the (200) plane of AlN, the (200) plane of TiN, the (220) plane of AlN, and the (220) plane of TiN, which have the fcc structure, and the peak intensities due to the (010) plane of AlN, the (011) plane of AlN, and the (110) plane of AlN, which have the hcp structure.
[0028] By evaluating the relationship between Ih and Is, the amount of hcp AlN in the microstructure can be quantitatively evaluated. A smaller Ih×100 / Is value means that there is less brittle hcp AlN in the microstructure. In this embodiment, a coated cutting tool having good durability is realized by configuring the hard coating to satisfy Ih×100 / Is≦12. Furthermore, it is preferable that the hard coating is configured such that no peak intensity due to the (010) plane of the hcp AlN is confirmed, that is, the hard coating is configured to satisfy Ih×100 / Is=10 or less. Even if the diffraction pattern of the hcp AlN is confirmed in the selected area diffraction pattern, if the amount is small, no peak appears in the intensity profile and the value of Ih×100 / Is may be 0.
[0029] The hard coating according to the present embodiment is likely to have a generally uniform structure when the content of Al is less than 78 atomic %. On the other hand, when the content of Al in the hard coating according to the present embodiment is 78 atomic % or more, or even 80 atomic % or more, the hard coating is likely to have a structure in which a region mainly made up of relatively coarse particles and a region mainly made up of relatively fine particles are mixed due to the influence of the surface condition of the substrate. A region mainly made up of relatively coarse particles tends to be formed on a smooth substrate. A region mainly made up of relatively fine particles tends to be formed on a substrate with many projections and recesses. In the present embodiment, the value of Ih×100 / Is is set to 12 or less in any region. In a region where relatively coarse particles are predominant, there tends to be relatively less AlN with hcp structure present in the microstructure. In a region where relatively coarse particles are predominant, the value of Ih×100 / Is is preferably 0 to 8. A region where relatively coarse particles are predominant tends to have excellent toughness. On the other hand, in a region where relatively fine particles are predominant, there tends to be relatively more AlN with hcp structure present in the microstructure. In a region where relatively fine particles are predominant, the value of Ih×100 / Is is preferably 4 to 12. A region where relatively fine particles are predominant tends to have excellent wear resistance. It is preferable that there are many regions where relatively fine particles are predominant.
[0030] <Average grain size> The hard coating according to the present embodiment preferably has an average crystal grain size of 5 nm or more. If the microstructure of the hard coating is too fine, the structure of the hard coating becomes close to amorphous, and the toughness is significantly reduced. In order to increase the crystallinity of the hard coating and reduce the brittle amorphous phase, the average crystal grain size of the hard coating is preferably 5 nm or more. More preferably, the average crystal grain size of the hard coating is 20 nm or more. In addition, if the microstructure of the hard coating becomes too coarse, the toughness is reduced and the fracture unit of the hard coating becomes large, resulting in greater damage to the tool. In order to increase the toughness of the hard coating and reduce the fracture unit to suppress tool damage, the average crystal grain size of the hard coating is preferably 100 nm or less. More preferably, the average crystal grain size of the hard coating is 80 nm or less. If the internal structure of the hard coating is significantly different, the strength of the hard coating is reduced. Therefore, even if the hard coating has a structure in which a region mainly made up of relatively coarse particles and a region mainly made up of relatively fine particles are mixed, the average crystal grain size of the region mainly made up of relatively coarse particles is preferably 1.2 to 4.0 times the average crystal grain size of the region mainly made up of relatively fine particles. More preferably, it is 3.0 times or less. The average crystal grain size of the hard coating according to this embodiment is measured by measuring the width of crystal grains in a direction perpendicular to the film thickness direction using a transmission electron microscope. It is preferable to measure the widths of 10 or more crystal grains and use the average value of the widths as the average crystal grain size.
[0031] <Droplet> In the hard coating according to this embodiment, droplets with a circle equivalent diameter of 1 μm or more are 100 μm in cross-section observation. 2 It is preferable that the number of droplets is 5 or less per 100 μm. In hard coatings coated by physical vapor deposition, droplets can be the main physical defect. In particular, coarse droplets with a circle equivalent diameter of 1 μm or more can be the starting point of fracture inside the hard coating, so the toughness of the hard coating can be increased by reducing the frequency of their occurrence. In this embodiment, droplets with a circle equivalent diameter of 1 μm or more are counted within 100 μm in cross-sectional observation of the hard coating. 2 It is preferable to set the number of particles per 100 μm or less.2 More preferably, the number of particles is 3 or less per 100 μm. 2 It is further preferred that the droplets do not contain droplets with an equivalent circle diameter of 5 μm or more. In addition, on the surface of the hard coating, droplets with a circle equivalent diameter of 1 μm or more were observed to be 100 μm in diameter. 2 More preferably, the droplets on the surface of the hard coating are 100 μm or less. 2 More preferably, the droplets on the surface of the hard coating are 100 μm or less. 2 There is less than one per prize. In this specification, the term "droplets" refers to deposits on a hard coating that result from metal particles of about 1 to several tens of μm that suddenly fly off from a target.
[0032] To evaluate droplets in cross-sectional observation of a hard coating, the hard coating is mirror-finished and then processed by a focused ion beam method to prepare an observation sample. Using a transmission electron microscope, the mirror-finished surface of the observation sample is observed in multiple fields of view at 5,000 to 10,000 times magnification. The number of droplets on the surface of the hard coating can be determined by observing the surface of the hard coating using a scanning electron microscope (SEM) or the like.
[0033] <Intermediate film> The hard coating according to this embodiment is preferably provided directly on the substrate. By providing the hard coating directly on the substrate, the crystallinity of the hard coating is increased, and it is more likely to obtain a crystal structure with a face-centered cubic structure. Although the mechanism is unclear, it is presumed that the surface condition of the substrate, the kinetic energy of the particles that reach the substrate and epitaxial growth on the substrate have an influence. The coated tool according to this embodiment is preferably provided directly on the substrate, since it can more stably suppress the generation of AlN with a micro-level hcp structure. Depending on the manufacturing conditions, even if an intermediate coating is provided, the increase of AlN with a hcp structure can be suppressed. Therefore, the coated tool according to this embodiment may be provided with an intermediate coating. For example, a layer made of any of metal, nitride, carbonitride, and carbide may be provided between the substrate and the hard coating of the tool.
[0034] <Hardness / elastic modulus> The hard coating according to this embodiment preferably has a nanoindentation hardness of 30 GPa or more and an elastic modulus of 500 GPa or more. This improves the hardness and elastic modulus of the hard coating, thereby improving the durability of the coated tool. Furthermore, the hard coating according to this embodiment preferably has a nanoindentation hardness of 35 GPa or more. The hard coating according to this embodiment preferably has an elastic modulus of 550 GPa or more.
[0035] <Upper layer> In the coated tool of the present embodiment, another hard coating having a different component ratio or composition from the hard coating of the present embodiment may be formed separately on the hard coating of the present embodiment.Furthermore, the hard coating of the present embodiment and another hard coating having a different component ratio or composition from the hard coating of the present embodiment may be mutually laminated.
[0036] <Manufacturing method> In the coating of the hard film according to the present embodiment, a sputtering method is applied in which three or more AlTi-based alloy targets are used, power is applied to the targets in sequence, and when the target to which power is applied is switched, a time is provided during which power is applied to both the target to which power application ends and the target to which power application starts at the same time. In such a sputtering method, the high ionization rate of the target is maintained during coating, and a fine and dense hard film is obtained at the micro level, and the amount of argon and oxygen inevitably contained tends to be small. In addition, it is preferable to set the temperature inside the furnace of the sputtering device to 200°C to 400°C, the negative pressure bias voltage applied to the substrate to -200V to -50V, and the furnace pressure to 0.1Pa to 0.4Pa by introducing Ar gas and N2 gas, in order to promote the ionization of the target components and nitrogen and reduce the hcp structure AlN at the micro level. In addition, when carbonitride is to be coated as the hard film, a small amount of carbon may be added to the target for forming the hard film, or a part of the reaction gas may be replaced with methane gas. In addition, in order to reduce the hcp structure of AlN at the micro level, it is effective to appropriately set the distance between the target and the substrate. By setting the minimum distance between the target and the substrate to 50mm to 100mm, the state of the plasma to which the substrate is exposed during coating becomes constant, and the face-centered cubic lattice structure tends to be easily formed.
[0037] The maximum power density of the power pulse is 0.5kW / cm 2 It is preferable that the power density applied to the target is 3.0 kW / cm or more. However, if the power density applied to the target is too high, it is difficult to stabilize the film formation. Also, if the power density is too high, the frequency of droplet generation tends to increase even in the sputtering method. Therefore, the maximum power density of the power pulse is 3.0 kW / cm. 2 It is preferable that the maximum power density of the power pulse is 2.0 kW / cm or less. 2 The average power density of the power pulse is preferably 0.10 to 0.30 kW / cm or less. 2The duration of the power pulse applied to each target is preferably 20 microseconds or more. Also, the duration during which power is simultaneously applied to both the alloy target to which power application is terminated and the alloy target to which power application is initiated is preferably 5 microseconds or more and 100 microseconds or less. EXAMPLES
[0038] In "Example 1", the film properties were evaluated. <Base material> As the substrate, a two-blade ball end mill (manufactured by MOLDINO CORPORATION) made of cemented carbide with the composition WC (bal.)-Co (8.0 mass%)-VC (0.3 mass%)-Cr3C2 (0.5 mass%) and hardness of 94.0 HRA (Rockwell hardness, value measured in accordance with JIS G 0202) was prepared.
[0039] In forming the hard films in Examples 1 to 5 and Comparative Examples 1 to 4, a sputtering device capable of mounting six sputter evaporation sources was used. Among these evaporation sources, three AlTi alloy targets were installed in the device as evaporation sources to coat the hard films. The targets used had a size of Φ16 cm and a thickness of 12 mm. For the hard coating, an Al85Ti15 alloy target (numerical values are atomic ratios, the same applies below) was used in Example 1. An Al80Ti10Cr10 alloy target was used in Example 2. An Al80Ti20 alloy target was used in Examples 3 to 5 and Comparative Examples 2 to 4. An Al75Ti25 alloy target was used in Comparative Example 1. For all samples, an Al60Ti40 alloy target was used for coating the intermediate coating.
[0040] The tool, which is the substrate, was fixed to the sample holder in the sputtering device, and a bias power supply was connected to the tool. The bias power supply was designed to apply a negative bias voltage to the tool independently of the target. The tool rotated at two revolutions per minute and revolved around the fixing jig and the sample holder. The gases used were Ar and N2, and were introduced from a gas supply port provided in the sputtering device. Regarding the tool installation method, in installation method 1, the shortest distance between each target and the substrate was set to 100 mm on average. In installation method 2, the shortest distance between each target and the substrate was set to 125 mm on average. In installation method 3, the shortest distance between each target and the substrate was set to 170 mm on average.
[0041] <Bombardment Processing> First, before coating the tool with a hard coating, the tool was bombarded in the following manner. The tool was heated for 30 minutes at a furnace temperature of 430°C using the heater in the sputtering device. After that, the sputtering device was evacuated and the furnace pressure was reduced to 5.0×10 -3 Pa or less. Then, Ar gas was introduced into the furnace of the sputtering device, and the pressure inside the furnace was adjusted to 0.8 Pa. Then, a DC bias voltage of -170 V was applied to the tool, and cleaning (bombardment) of the tool was performed with Ar ions.
[0042] <Hard coating> Next, the furnace temperature was set to the set temperature, and Ar gas and N2 gas were introduced into the furnace of the sputtering device to adjust the furnace pressure. Then, power was continuously applied to the three AlTi-based alloy targets to coat an intermediate film of about 0.2 μm consisting of Al and Ti nitrides with an fcc structure. Next, a DC bias voltage was applied to the substrate, the overlap time of the power applied to the target was set to 10 microseconds, and the discharge time per cycle of the power applied to the target was adjusted. Then, power was continuously applied to the three AlTi-based alloy targets to coat the surface of the substrate with a hard film of about 3.0 μm.
[0043] An arc ion plating device was used to form the hard coating of Comparative Example 5. An AlTi alloy target was placed in the device as a deposition source. The target had a diameter of 16 cm and a thickness of 12 mm. In the same manner as the film formation process of the hard film of Example 1, cleaning of the tool (bombardment treatment) with Ar ions was carried out. Next, the pressure inside the arc ion plating apparatus was evacuated to 5.0×10 -3 Pa or less, the temperature inside the furnace was set to 500 °C, and N2 gas was introduced so that the pressure inside the furnace became 4.0 Pa. Next, a DC bias voltage was applied to the substrate, a current of 150 A was applied to the AlTi-based alloy target, and a hard film of about 3.0 μm was coated on the surface of the tool. The film formation conditions for each sample are summarized in Table 1.
[0044]
Table 1
[0045] <Film composition> The film composition of the hard film was measured by wavelength-dispersive electron probe microanalysis (WDS-EPMA) attached to an electron probe microanalyzer (JXA-8500F manufactured by JEOL Ltd.). A ball end mill for physical property evaluation was mirror-finished, with an acceleration voltage of 10 kV, an irradiation current of 5×10 -8 A, an integration time of 10 seconds, and the analysis area was measured at 5 points in a range with a diameter of about 1 μm, and the metal content ratio of the hard film and the argon content ratio in the total of the metal component and the non-metal component were determined from the average value.
[0046] <X-ray analysis> The crystal structure of the hard film was confirmed using an X-ray diffractometer (EMPYREA manufactured by PaNalytical) under the measurement conditions of a tube voltage of 45 kV, a tube current of 40 mA, an X-ray source Cukα (λ = 0.15405 nm), and 2θ from 20 to 80 degrees.
[0047] <Film hardness and elastic modulus> The film hardness and elastic modulus of the hard film were analyzed using a nanoindentation tester (ENT-2100 manufactured by Elionix, Inc.). For the analysis, after mirror-polishing the film cross-section where the test piece was tilted 5 degrees with respect to the outermost surface of the film, a region where the maximum indentation depth was less than approximately 1 / 10 of the film thickness was selected within the polished surface of the film. Ten measurements were taken under the measurement condition of an indentation load of 9.8 mN / second, and the value was determined from the average value of six points excluding the two points on the larger value side and the two points on the smaller value side.
[0048] <TEM analysis> The selected area diffraction pattern of the hard film was obtained under the conditions of an acceleration voltage of 200 kV, a selected area region of φ1000 nm or more, a camera length of 100 cm, and an incident electron amount of 5.0 pA / cm 2 (on the fluorescent screen). The brightness of the obtained selected area diffraction pattern was converted to obtain an intensity profile. The analysis location was near the center in the film thickness direction of the hard film. The results of the physical property evaluation are summarized in Table 2.
[0049]
Table 2
[0050] Fig. 1 shows an example of a cross-sectional observation photograph by TEM of a hard film having a region mainly composed of relatively coarse particles and a region mainly composed of relatively fine particles relative to Fig. 1. The vicinity of (a) in Fig. 1 is a region mainly composed of relatively coarse particles, and the vicinity of (b) is a region mainly composed of relatively fine particles. Fig. 2 shows an example of an enlarged photograph of the region mainly composed of relatively coarse particles in Fig. 1. Fig. 3 is an example of a selected area diffraction pattern in the region mainly composed of relatively coarse particles. Fig. 4 is an example of a diagram showing the intensity profile of the selected area diffraction pattern shown in Fig. 3. Fig. 5 shows an example of an enlarged photograph of the region mainly composed of relatively fine particles in Fig. 1. Fig. 6 is an example of a selected area diffraction pattern in the region mainly composed of relatively fine particles. Fig. 7 is an example of a diagram showing the intensity profile of the selected area diffraction pattern shown in Fig. 6. Ih×100 / Is was calculated from the intensity profiles shown in Figures 4 and 7. As a result, it was confirmed that the value of Ih×100 / Is was smaller in areas dominated by relatively coarse particles than in areas dominated by relatively fine particles.
[0051] The hard coating of Example 1 had a structure having an area mainly composed of relatively coarse particles and an area mainly composed of relatively fine particles. The hard coatings of the other Examples had a structure in which the particle size was generally uniform, and the value of Ih×100 / Is was 10 or less. In the hard coatings of all Examples, the peak intensity of AlN with hcp structure was not confirmed by X-ray diffraction, and AlN with hcp structure was confirmed slightly at the micro level. The hard coatings of Examples 1 to 5 all had an argon content of 0.10 atomic % or less. In addition, in cross-sectional observation, droplets with a circle equivalent diameter of 1.0 μm or more were found to be 100 μm or more in diameter. 2 No droplets with an equivalent circle diameter of 5.0 μm or more were observed. It was confirmed that the hard coatings of all the examples were Al-rich, but had few defects such as hcp AlN, droplets, and argon. It was confirmed that the hard coatings of Examples 1 to 5 had a nanoindentation hardness of 30 GPa or more and an elastic modulus of 500 GPa or more.
[0052] Fig. 8 shows an example of a cross-sectional photograph taken by a transmission electron microscope of the hard coating of Comparative Example 1. Fig. 9 is an example of a diagram showing the selected area diffraction pattern in Fig. 8. Fig. 10 is an example of a diagram showing the intensity profile of the selected area diffraction pattern shown in Fig. 9. For the hard coatings of Comparative Examples 1 to 4, the peak intensity of AlN with hcp structure was confirmed by X-ray diffraction, and the value of Ih×100 / Is was also larger than that of the Examples. For Comparative Examples 2 and 4, the peak intensity of the fcc (111) plane was not confirmed by X-ray diffraction. The argon content was also higher than that of the Examples. For the hard coating of Comparative Example 4, the structure had a region mainly composed of relatively coarse particles and a region mainly composed of relatively fine particles, and in the region mainly composed of relatively coarse particles, Ih×100 / Is=0, but in the region mainly composed of relatively fine particles, Ih×100 / Is=24. It was confirmed that the hard coatings of Comparative Examples 1-4 had more defects caused by either or both of the hcp AlN structure and the high concentration of argon, compared to the hard coatings of Examples 1-5. It was confirmed that the hardness and elastic modulus of Comparative Examples 1 to 4 were lower than those of Examples. That is, it was confirmed that when any one or more of the bias voltage, film formation temperature, and installation method are out of the appropriate range, the number of defects in the obtained hard coating tends to increase, and as a result, the hardness and elastic modulus of the hard coating are easily reduced. The hard coating of Comparative Example 5 was formed by arc ion plating and contained many coarse droplets. EXAMPLES
[0053] In "Example 2", cutting evaluation was carried out for the end mills of Example 1, Example 4 and Comparative Example 5 used in "Example 1". The machining conditions were as follows. The evaluation results are summarized in Table 3. (Condition) Dry processing Tool: 2-blade carbide ball end mill Model number: EPDBE2010-6, ball radius 0.5mm Cutting method: bottom cutting Work material: STAVAX (52HRC) (manufactured by BOHER-Uddeholm Co., Ltd.) Cut: Axial, 0.03mm, Radial, 0.03mm Cutting speed: 67.8m / min Feed per blade: 0.0135mm / blade Cutting distance: 15m Evaluation method: After cutting, the workpiece was observed at a magnification of 1000x using a scanning electron microscope, the width of the abrasion between the tool and the workpiece was measured, and the part with the largest abrasion width was recorded as the maximum wear width.
[0054] [Table 3]
[0055] It was confirmed that the hard coatings of Examples 1 and 4 were Al-rich and had few defects such as hcp-structured AlN, droplets, and Ar inside the coating, and therefore suppressed tool wear more than the hard coating of Comparative Example 5 produced by the conventional arc ion plating method. In particular, it is presumed that the hard coating of Example 1 had a region mainly composed of relatively fine particles, which further suppressed the maximum flank wear width. EXAMPLES
[0056] In "Example 3", the intermediate coating was evaluated. In "Example 3", an Al80Ti20 alloy target was used for depositing the hard coating. In the sample preparation process of Example 30, the hard coating was coated directly on the substrate. In the sample preparation process of Comparative Example 30, similar to the sample preparation process of Example 1, the intermediate coating was coated on the substrate surface, and then the hard coating was coated. The deposition conditions for each sample are summarized in Table 4.
[0057] [Table 4]
[0058] [Table 5]
[0059] The coating conditions of the hard coating are the same in Example 30 and Comparative Example 30. In Example 30, in which the hard coating is provided directly on the substrate, a hard coating having a small amount of hcp-structured AlN at the micro level is obtained, but in Comparative Example 30, in which the hard coating is provided via an intermediate coating, a peak of hcp-structured AlN is confirmed in the X-ray diffraction of the hard coating. By comparing Example 30 and Comparative Example 30, it was confirmed that when a hard coating is applied under the same conditions, coating the hard coating directly on the substrate without providing an intermediate coating makes it easier to make the crystal structure of the hard coating have a face-centered cubic structure, and tends to result in less AlN with a hcp structure.
Claims
1. A coated cutting tool having a substrate and a hard coating on the substrate, The hard coating is a sputtering coating, The hard coating contains aluminum (Al) at 65 atomic % or more and 90 atomic % or less, titanium (Ti) at 10 atomic % or more and 35 atomic % or less, and the total of aluminum (Al) and titanium (Ti) at 85 atomic % or more, based on the total amount of metal (including metalloid) elements; A nitride or carbonitride containing argon (Ar) in an amount of 0.20 atomic % or less based on the total amount of metal elements (including metalloids) and nonmetal elements, the hard coating is characterized in that, in an intensity profile obtained from a selected-area diffraction pattern under a transmission electron microscope, the hard coating satisfies the relationship Ih×100 / Is≦12, where Ih is a peak intensity due to an AlN (010) plane having a hexagonal close-packed structure, and Is is the sum of peak intensities due to the AlN (111) plane, the TiN (111) plane, the AlN (200) plane, the TiN (200) plane, the AlN (220) plane, and the TiN (220) plane, which are of a face-centered cubic lattice structure, and peak intensities due to the AlN (010) plane, the AlN (011) plane, and the AlN (110) plane, which are of the hexagonal close-packed structure.
2. 2. The coated cutting tool according to claim 1, wherein the hard coating has a structure having an area mainly made up of relatively coarse particles and an area mainly made up of relatively fine particles.
3. 3. The coated cutting tool according to claim 2, characterized in that the region mainly composed of relatively coarse grains has an average crystal grain size that is 1.2 to 4.0 times the average crystal grain size of the region mainly composed of relatively fine grains.
4. 4. The coated cutting tool according to claim 3, characterized in that in the region mainly composed of relatively coarse particles, the value of Ih×100 / Is is 0 or more and 8 or less, and in the region mainly composed of relatively fine particles, the value of Ih×100 / Is is 4 or more and 12 or less.
5. 5. The coated cutting tool according to claim 1, wherein the hard coating is provided directly on the substrate.
6. 6. The coated cutting tool according to claim 1, wherein the hard coating has a nanoindentation hardness of 30 GPa or more and an elastic modulus of 500 GPa or more.
Citation Information
Patent Citations
Antenna device
JP1981073904A
Wear resistant film coated member
JP1996209333A
Alti series alloy sputtering target, wear resistant alti series alloy hard film and formation of the film
JP2000297364A
Surface coated-thermet cutting tool having cutting blade face of low frictional resistance to chip
JP2001179502A
Coated tool excellent in wear resistance
JP2011189419A